2015
DOI: 10.1002/ab.21597
|View full text |Cite
|
Sign up to set email alerts
|

A dangerous boomerang: Injunctive norms, hostile sexist attitudes, and male‐to‐female sexual aggression

Abstract: This study examined the interactive effects of injunctive norm exposure and hostile and benevolent sexist attitudes on men's sexually aggressive responses during a behavioral analogue paradigm in which they interacted online with a bogus female partner. Heterosexual adult men (n = 201), recruited from an online sample, read fictional information regarding other men's approval of misogynistic, paternalistic, or egalitarian treatment of women, or non-gender-relevant control information. Through a media preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 68 publications
1
55
0
Order By: Relevance
“…Attitudes condoning violence are consistently associated with boys' TDV perpetration (Foshee et al, 2001; Reyes et al, 2016). Similarly, given pervasive hegemonic gender socialization messages in our culture mandating boys and men to be strong, dominant, and superior to women, it is likely victimization by girls could fuel anti-feminine attitudes and hostility thereby precipitating future IPV/TDV by males as a means of maintaining dominance over women (Bosson et al, 2015; Malamuth et al, 1995; Smith et al, 2015). Thus, the relatively small sex differences in perpetration identified in the present sample may grow with age increasing the disparity in perpetration as boys physically mature into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes condoning violence are consistently associated with boys' TDV perpetration (Foshee et al, 2001; Reyes et al, 2016). Similarly, given pervasive hegemonic gender socialization messages in our culture mandating boys and men to be strong, dominant, and superior to women, it is likely victimization by girls could fuel anti-feminine attitudes and hostility thereby precipitating future IPV/TDV by males as a means of maintaining dominance over women (Bosson et al, 2015; Malamuth et al, 1995; Smith et al, 2015). Thus, the relatively small sex differences in perpetration identified in the present sample may grow with age increasing the disparity in perpetration as boys physically mature into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Those concerned about an issue frequently attempt to motivate change by publicizing the size of the problem: “1 in 3 women globally are abused by their partner”; or: “The average American intakes 44.7 gallons of sugary soda each year”. Because descriptive norms (beliefs about what others do) can influence people’s behaviour, such campaigns can unwittingly reinforce a practice [ 15 , 107 , 108 ]. Even though this point is quite well established in the theoretical and empirical literature, there are still questions about how this finding can inform effective interventions.…”
Section: Eight Pitfalls Of Social Norms Interventionsmentioning
confidence: 99%
“…Some prior research has found that injunctive norms may have an influence on behavior even in situations where descriptive norms do not (Henry et al., ; Moon, Weick, & Uskul, ). Numerous prior studies have documented associations between youths’ perceptions of injunctive norms and substance use (Nesi, Rothenberg, Hussong, & Jackson, ; Stanley, Swaim, & Dieterich, ) and aggression perpetration (Ajzen, ; Bosson, Parrott, Swan, Kuchynka, & Schramm, ; Hertzog & Rowley, ; Reyes, Foshee, Niolon, Reidy, & Hall, ). The robust relationship between perceptions of peers’ expectations for behavior and individuals’ actual behavior has been attributed to the human tendency to want to be perceived as behaving “normally”—that is, neither above or below the norm (Hertzog & Rowley, ; Schultz, Nolan, Cialdini, Goldstein, & Griskevicius, ).…”
Section: Introductionmentioning
confidence: 99%